HUBUNGAN MUTU, INDIKATOR KINERJA KUNCI, DAN KINERJA PELAYANAN RUMAH SAKIT (STUDI KASUS PADA RUMAH SAKIT AUMAKES) - Arlina Dewi; Aris Suparman Wijaya; Fradita Eka Sukardi (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2013)
Background: Muhammadiyah and 'Aisha had a vision of 2020 is going to be a major driver of the establishment of networks between social groups that support healthy communities self-reliant and vision of 2015. Thus conducted a study of 40 hospitals under the auspices of Aumakes in 2009, from that data, researchers interested in conducting research on the quality of 40 hospitals under the auspices of Aumakes. Purpose: The research objective is 1). To analyze the relationship of the hospital quality with Key Performance Indicators (KPI), 2) to analyze the relationship of the Hospital Quality with BOR and 3). To analyze the relationship of the hospital quality with ALOS. Methods: Types of research taking secondary data in 2009 with the design of the quantitative analysis method of retrospective study. Location of the study in 40 hospitals under the auspices of Aumakes. Analyzed using quantitative with correlation statistical program. Result:. Correlation statistical data shows significant relationship exists between the quality and KPI with significance values is 0.00 and with strong correlation is 0.719. There is a significant relationship between hospital quality and BOR with significant value is 0.016 by weak correlation 0.394. There was no significant relationship between the quality and ALOS which is significance values 0.831.